Case Report: Left bundle branch pacing in an amyloid light-chain cardiac amyloidosis patient with atrioventricular block - Yu, Jiaqi; Kong, Fanyi; Gao, Peng; Chen, Taibo; Liu, Yongtai; Cheng, Zhongwei; Deng, Hua; Lai, Jinzhi; Zhang, Lihua; Fan, Jingbo; Wang, Jiaqi; Qin, Xiaohan; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Amyloid light-chain cardiac amyloidosis is a progressive infiltrative disease characterized by the deposition of amyloid fibrils in the cardiac tissue, which can cause serious atrioventricular block requiring pacemaker implantation. Left bundle branch pacing has emerged as an alternative method for delivering physiological pacing to achieve electrical synchrony of the left ventricle. However, left bundle branch pacing in patients with amyloid light-chain cardiac amyloidosis has not been studied in detail. Therefore, in this study, we present a case of left bundle branch pacing in a patient with amyloid light-chain cardiac amyloidosis. Case summary A 66-year-old male patient with amyloid light-chain cardiac amyloidosis presented with syncope for 1 month. Holter monitoring revealed intermittent third-degree atrioventricular block. Left bundle branch pacing was performed successfully. During the 1-year follow-up, it was observed that the left bundle branch capture threshold remained stable without any pacemaker-related complications or left ventricle systolic dysfunction, and there was no recurrence of syncope. Conclusion Left bundle branch pacing appears to be a safe and feasible option for patients with amyloid light-chain cardiac amyloidosis experiencing atrioventricular block.